Noninvasive prenatal test for FGFR3‐related skeletal dysplasia based on next‐generation sequencing and plasma cell‐free DNA: Test performance analysis and feasibility exploration. (19th August 2018) - Ren, Yuan; Zhao, Jia; Li, Ruibing; Xie, Yifan; Jiang, Shufang; Zhou, Honghui; Liu, Hongtai; You, Yanqin; Chen, Fang; Wang, Wei; Gao, Ya; Meng, Yuanguang; et al.
Abstract: Objective: To explore the feasibility and accuracy of a noninvasive prenatal test for fibroblast growth factor receptor 3 ( FGFR3 )‐related skeletal dysplasia based on next‐generation sequencing (NGS) of plasma cell‐free DNA. Method: Fragmented genome DNA (gDNA) of fetuses with achondroplasia (ACH) and thanatophoric dysplasia type I (TD I) was mixed with postdelivery maternal plasma cell‐free DNA to generate spiked samples of different modeled fetal fractions. Multiplex polymerase chain reaction was used to amplify the 19 FGFR3 loci, and the amplification products were then sequenced by NGS to detect the fetal mutant alleles. Then, maternal plasma samples of pregnant women carrying ACH ( n = 4) and TD I fetuses ( n = 2), as well as healthy controls ( n = 15), were tested by NGS, and the test performance was evaluated. Results: Fetal FGFR3 mutations were detected in all artificial mixtures with fetal gDNA concentrations above 3%. In clinical validation, our method identified all fetal FGFR3 mutant alleles from maternal plasma, with no false positive results. The sensitivity and specificity of our method were 100% (95% CI, 54.1%‐100%) and 100% (78.2%‐100%), respectively. Conclusion: Our method had a favorable performance for noninvasively detecting fetal FGFR3 mutations in maternal plasma, highlighting its promising value in developing a noninvasive prenatal test for de novo and paternally inherited disorders. Abstract : What's already known about this topic? Early prenatal diagnosis of FGFR3 ‐related diseases is important for pregnancy management. Noninvasive prenatal testing for fetal FGFR3 ‐related skeletal dysplasia using maternal plasma by different approaches has been previously reported. Of those, next‐generation sequencing (NGS) has been shown to be more reliable and flexible. However, more evidence of the test performance using NGS, especially in early gestation, is still needed. What does this study add? The test performance and accuracy of NGS‐based detection of fetal FGFR3 mutations from maternal plasma was very favorable, both early and late in gestation. This supports the possibility of introducing noninvasive prenatal testing at early stages of gestation for FGFR3 ‐related skeletal dysplasia and in the future other de novo and paternal inherited diseases.